The Development of Student Engagement Scale in Vocational High School Students - Hanun Adinayya Najwa; Syafruddin Faisal Thohar (International Conference on Sustainable Health Promotion, 2025)
This study aims to develop a student engagement scale by testing the validity and reliability of the measuring instrument so that it can measure the level of student engagement. Student engagement is a factor that determines student success in academic terms, including behavioral, cognitive, and emotional involvement. The research method used is quantitative research. Data collection using convenience sampling obtained 315 students at SMK Pawiyatan Surabaya. Data analysis used validity and reliability tests, including confirmatory factor analysis (CFA). The results showed a Cronbach's Alpha value of 0.888, consisting of 34 items. In addition, CFA analysis using a GFI value of 0.960 and an RMSEA of 0.072 showed that the student engagement scale had high validity. However, the CFI value of 0.716 indicates that the student engagement measurement tool is not sufficiently reliable, requiring improvement so that the student engagement scale can be used optimally.